Role of Teachers in Technology-mediated Distance Education: A Preliminary Synthesis - Dave, Deeksha (International Journal on Open and Distance e-Learning, 2017)
Technological advances in distance education have transformed the teaching learning processes. It has been realised that there are innumerable possibilities of using educational technology as a crucial pedagogical resource during teaching and learning. Technology has expanded the opportunities for students to access higher education but on the other hand it has presented challenges before the teachers to devise creative methods of teaching. Distance education today demands a change in the role of teachers so that meaningful leaner-centric interactions and discussions take place. However, at several occasions it is feared particularly in distance education systems that technology would replace teachers. In this context, it is necessary that teachers in distance education make use of the latest educational technologies as a resource to carry out effective teaching. In view of this, an attempt has been made in the current paper to explore the role of teachers in technology mediated distance education. The paper finally asserts that effective faculty participation is the key driving factor towards the success of technology- mediated distance education.